2022
DOI: 10.3390/buildings12050537
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Impact of Urban Planning and Building Typologies in Urban Heat Island Mitigation

Abstract: Urban and building typologies have a serious impact on the urban climate and determine at large the magnitude of the urban overheating and urban heat island intensity. The present study aims to analyze the impact of various city typologies and urban planning characteristics on the mitigation of the urban heat island. The effect of the building height, street width, aspect ratio, built area ratio, orientation, and dimensions of open spaces on the distribution of the ambient and surface temperature in open space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Moreover, the categorization through urban typological analysis can help identify areas that need improvement or revitalization. By analyzing the different categories of urban elements, it is possible to identify areas that lack infrastructure, public spaces, or green elements and develop strategies to fill these gaps [34]. In the case of Ferencváros, typological study revealed the municipality's renovation strategy, which involved prioritizing the renovation or replacement of existing urban sub-elements to achieve a more cohesive urban fabric.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the categorization through urban typological analysis can help identify areas that need improvement or revitalization. By analyzing the different categories of urban elements, it is possible to identify areas that lack infrastructure, public spaces, or green elements and develop strategies to fill these gaps [34]. In the case of Ferencváros, typological study revealed the municipality's renovation strategy, which involved prioritizing the renovation or replacement of existing urban sub-elements to achieve a more cohesive urban fabric.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing urban water bodies and blue infrastructures promotes evaporative cooling and reduces urban heat island effects (Krüger, 2021 ; Sharma et al 2022 ). Yet, these infrastructures would better be carefully designed and fitted into city planning to maximum the effectiveness (Kolokotsa et al 2022 ). Infrastructural modifications including building materials to increase surface albedo and decrease heat absorption are also mitigation measures (Krüger, 2021 ; Sharma et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated a strong correlation between the gradient of temperature decrease along the precinct axis (GTD) and the average aspect ratio of the precincts, regardless of whether mitigation strategies were implemented. As a result, the study suggests that implementing urban design interventions that modify the aspect ratio of buildings and streets can effectively mitigate the UHI effect and improve thermal comfort in open spaces [21].…”
Section: Uhi Effect and Surface Temperature Studiesmentioning
confidence: 91%